Symplastic leiomyoma: a rare clinicopatholgical diagnosis - Shenoy, Kavitha V.; N., Usha; Priyadarshini, Sarah Grace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Although leiomyomas are common this case is being reported due to its uniqueness as it posed challenges at all levels of pathological rarity and management. Symplastic leiomyoma is an unusual benign variant of leiomyoma with less likelihood of malignant transformation. In our case report we present a 28-year-old nulligravida who presented to our OPD with Fibroid uterus detected on scan and myomectomy specimen done revealed a rare pathological diagnosis of symplastic leiomyoma and her followup.